Toward Evidence Based Practice. Issue 1 (January 2015) - Hayman, Laura L.; Lewis, Judy A.; Lewis, Judith A.
<x xml:space="preserve">Abstract</x> Experts suggest how 6 research articles can be used in nursing practice.